Factors considered important by managers to gaining employment in high performance sport: A survey of high performance sports programs - Sakadjian, A. (Journal of Australian Strength and Conditioning, 2018)
Strength and conditioning (S&C) coaches are key members of professional sports programs charged with keeping athletes injury free and performing optimally. Despite these positions being common within professional sports programs and the important responsibilities associated with them, there is limited information available about the requirements to, firstly, be employed in these roles and, secondly, to perform well in such roles. The aims of this investigation were to obtain the minimum criteria required to be considered for employment in S&C based roles by current managers in professional sport. Survey A was sent to 74 high performance managers (HPM) with 58 responses received (78.4% response rate). Practical coaching experiences with athletes received 100% of responses as the priority for new graduates. Having a passion for S&C was ranked as the most valued quality in aspiring S&C coaches. An undergraduate degree (62.5%) was the minimum level of qualification required for junior roles while for senior roles there was an equal number of responses for undergraduate and master`s qualification (35.7% each). 66.1% of responses suggested 3+ years full time experience as the minimum requirement for senior S&C roles. 76.8% of responses rated being an ASCA accredited coach as the most valued industry based accreditation to obtain. Survey B was sent to a combination of 97 general managers and head coaches with 51 responses received (response rate = 52.6%). The most valued quality was being a sound communicator across diverse groups, while having people management experience was the minimum level of experience required by 41.1% of respondents. Head coach`s and general managers were adamant that the importance of the HPM role would continue to increase into the future.